FIKIH TOLERANSI - Agus Susanto (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
Tolerance is convenience, while in terminology the attitude of respect and acceptance of a choice, as well as the basic concepts of fiqh which are in accordance with human instincts, basically humans are tolerant and not intolerant. In the discipline of tolerance always accompanies human life wherever and whenever because Jurisprudence uses it as the main foundation in formulating a law and applies in all chapters in Jurisprudence both in the chapter worship, merryed, jinayah, social, political, health and so on, as in ubudiyyah chapter; humans in doing prayer fardlu if unable to stand can be done by sitting, and if sitting is not able to do it can be done by lying down and so on, all of that as a tolerant fiqh attitude towards the people in doing worship. Tolerance has been known for a long time and its relevance remains valid in the modern era.